Exenatide effects on gastric emptying rate and the glucose rate of appearance in plasma: A quantitative assessment using an integrative systems pharmacology model. Issue 8 (9th May 2018) - Voronova, Veronika; Zhudenkov, Kirill; Penland, Robert C.; Boulton, David W.; Helmlinger, Gabriel; Peskov, Kirill
Abstract : This study aimed to quantify the effect of the immediate release (IR) of exenatide, a short‐acting glucagon‐like peptide‐1 (GLP‐1) receptor agonist (GLP‐1RA), on gastric emptying rate (GER) and the glucose rate of appearance (GluRA), and evaluate the influence of drug characteristics and food‐related factors on postprandial plasma glucose (PPG) stabilization under GLP‐1RA treatment. A quantitative systems pharmacology (QSP) approach was used, and the proposed model was based on data from published sources including: (1) GLP‐1 and exenatide plasma concentration‐time profiles; (2) GER estimates under placebo, GLP‐1 or exenatide IR dosing; and (3) GluRA measurements upon food intake. According to the model's predictions, the recommended twice‐daily 5‐ and 10‐μg exenatide IR treatment is associated with GluRA flattening after morning and evening meals (48%‐49%), whereas the midday GluRA peak is affected to a lesser degree (5%‐30%) due to lower plasma drug concentrations. This effect was dose‐dependent and influenced by food carbohydrate content, but not by the lag time between exenatide injection and meal ingestion. Hence, GER inhibition by exenatide IR represents an important additional mechanism of its effect on PPG.